Drought : the past, present, and future enemy - Dolan, Edward F., 1924- (New York : F. Watts, 1990)
Discusses the causes and effects of droughts and examines the possibility of future droughts due to such phenomena as the greenhouse effect. Also discusses weather modification as a solution to this problem.
Includes bibliographical references.
Booklist.
Voice of Youth Advocates (V.O.Y.A.).
Wilson's Junior High School.
Young Adult.
Young Adult
Keywords: Droughts; Droughts; Droughts